Direito à felicidade: história, teoria, positivação e jurisdição - Leal, Saul Tourinho (2013)
This thesis has the purpose to investigate whether there are connections between the contemporary constitutionalism and happiness. It addresses the Independence of the United States of America, the French Revolution and the independence of Brazil. After such historical perspective, it describes the utilitarian school, represented initially by Jeremy Bentham and, subsequently, by Stuart Mill. It asserts that utilitarianism, allied to the principle of human dignity, is the theoretical basis of the thesis that allows happiness to be a constitutionally protected right and, moreover, providing the basis for it to appear in legal reasoning developed by the judges as grounds for judicial decisions. Subsequently, this thesis examines a dogmatic part in which it attempts to identify the existence of a right to happiness within the wording of the Constitution of 1988. In this part, it describes a right to happiness dismembered into five biases: (i) broad right to happiness, (ii) the right to the pursuit of happiness, (iii) the right to be provided with happiness (iv) sealing the perverse pleasures, (v) happiness as telos. Addressing the constitutional jurisdiction, it examines the American and European-continental models then shows how the theory of happiness has been used in trials of major national issues in Brazil, like the same-sex unions, policy of quotas, the Marijuana March and crimes trifle. It also discusses the abuses committed by invoking the theory of happiness, illustrating with the example of the Kingdom of Bhutan. Finally, it presents the proposal of hedonic damages. The thesis concludes there is a legally guaranteed right to happiness , but alerts that the theory of happiness is not able to solve all the cases, indicating that, in situations in which there are informational deficits, it is recommended judicial restraint and deference to the Legislature